IDENTIFIKASI BAHAN PEWARNA NAPHTHOL YELLOW S (C10H6N2NaO8S+) DALAM SEDIAAN PERONA MATA SECARA KROMATOGRAFI LAPIS TIPIS (KLT) - Oktania Hartina; Ulil Amna; Rahmatul Fajri (JURNAL QUIMICA, 2020)
Naphtol yellow S is a synthetic dye used for coloring batik. In cosmetics, naphtol yellow S is abused for eye shadow coloring to get more attractive colours, even though the use of naphtol yellow S can cause negative effects such as eye and respiratory tract irritation, dangerous if swallowed or inhaled will cause blood to become abnormal and followed liver and kidney damage. This study aims to identify naphtol yellow S in eye shadow. The coloring agent analysis was determined by Thin Layer Chromatography (TLC). Based on the result, there were no naphtol yellow S stains found in the sample. It can be concluded that the eye shadow samples used did not contain naphtol yellow S. Keywords: Naphtol Yellow S, Cosmetics, Eye Shadow, TLC